Sclerostin expression and functions beyond the osteocyte - Weivoda, Megan M. (Bone, 2016)
Sclerostin, the product of the SOST gene, is a secreted inhibitor of Wnt signaling that is produced by osteocytes to regulate bone formation. While it is often considered an osteocyte-specific protein, SOST expression has been reported in numerous other cell types, including hypertrophic chondrocytes and cementocytes. Of interest, SOST/sclerostin expression is altered in certain pathogenic conditions, including osteoarthritis and rheumatic joint disease, and it is unclear whether sclerostin plays a protective role or whether sclerostin may mediate disease pathogenesis. Therefore, as anti-sclerostin antibodies are being developed for the treatment of osteoporosis, it is important to understand the functions of sclerostin beyond the regulation of bone formation.